KRITIK ISLAM TERHADAP KONSEP MARXISME TENTANG PENGENTASAN KEMISKINAN - Bahtiyar, Eko; M. Mu’inudinillah, M. Mu’inudinillah; Hidayat, Syamsul (Profetika, 2015)
As a social reality, poverty canât be eliminated in absolute terms, but can be addressed and improved quality so it does not destroy humanity. Poverty as a reality of life is always described as a state of life that lacked, weak and helpless to meet their needs, both in terms of spiritual and material. The purpose of this study was to conceptualize poverty according to Marxism, and also to criticize that concept from Islam viewpoint as a religion. This study includes the type library research (library research), such as; the data and study materials including used from literature sources, either in the form of books, encyclopedias, journals, magazines, newspapers, and other papers. The form of this research is descriptive-comparative-analytical. So I can describe comprehensively thought Marxism and Islamic Thought about poverty alleviation. Discussion of the analysis of research conducted that research results obtained to alleviate poverty Marxist group should abolish bourgeois classes, banning private ownership, provocative investigation of the proletariat to the bourgeoisie attack, creating a battle between classes with spreading malice and hostility. Marx also consider religion and the state as a tool used by the borgeosie to increase their profits. All theories owned Marx is wrong and irrelevant to the truth. Islam stricly prohibitsthe hostilities and the destruction of certain communities. Islam also recognizes the right of property ownership. Goverment and religious factors also have an important rolein poverty alleviation. Islam teaches poor classes for hard-working, for the rich classes to tithe and cooperation between two classes. Keywords: poverty; marxism; Islam.